Application of reliability and maintainability analysis in the Svea coal mine - Furuly, Simon Andre (Universitetet i Tromsø, 2012)
The field of reliability engineering is developing, as needed in the industry. This is especially in arctic regions which now are being explored and vast recourses and opportunities are found. The reliability research is limited in the arctic, little knowledge is known about operating in the arctic regions. This research study will analyze equipment in an arctic region, Svalbard. It calculates the effects of operational conditions and the availability of a conveyor system found in a coal mine in Svalbard. The aim of the thesis is to understand the availability for the system and try to make a practical impact on the operations in the coal mine. The study has used two types of reliability methods – parametric and non-parametric method. These approaches can be used to find the reliability with and without the operational conditions included in the analysis. Similar for both methods are that they depend heavily on the data available. It seems that the operational conditions data collection is rare or non-existing. The study has produced two papers in order to analyze the main conveyor systems and a Stacker. It found for one year of operation (2010) that the availability was 96,44%. Although this is a high availability, it was found that the reliability was low. A second analysis was done on the Stacker with consideration of operational conditions. It was found that during the winter season the hazard rate increased by 4,78 times the design conditions. It was also found that if the Stacker’s performance operated like the other conveyors, this could save the company more than 3 million dollars. Some improvement measures are discussed for the data collection of failure and covariate data. The result presents an application of reliability and maintainability which seems to be useful for the operations in Svea.